Investigation of Moral Literacy Levels of University Students (The Case of Mus Alparslan University) - Fatma BİLDİRİCİ; Teceli KARASU (Din ve Bilim Muş Alparslan Üniversitesi İslami İlimler Fakültesi Dergisi)
This study examined the moral literacy levels of university students in terms of various variables (gender, grade level, and faculty type). The research was conducted on 423 students who were determined by convenience sampling method among the students studying at the Faculty of Education, Islamic Sciences, Sports Sciences and Arts and Sciences at Mus Alparslan University in the spring semester of the 2023-2024 academic year. Before the research, the ethics committee approval dated 10.05.2024 and numbered 141173 was obtained from Muş Alparslan University Scientific Research and Publication Ethics Committee. “Personal Information Form” and the ‘Moral Literacy Scale’ developed by Tekin (2022) were used as data collection tools in the study, which was conducted with the relational survey model, one of the quantitative research methods. This scale consists of five sub-dimensions and 20 items, including “Moral Reasoning” (4 items), “Moral Awareness” (5 items), “Moral Imagery” (5 items), “Moral Sensitivity” (3 items), and “Moral Determination” (3 items) to determine the moral literacy levels of individuals. There are no reverse coded items in the scale. The data obtained from the study was analyzed with the SPSS 22 statistical package program. Cronbach Alpha internal consistency coefficient was used in the reliability analysis of the scale. The Cronbach Alpha coefficient value of the scale was found as .87 for the "Moral Reasoning" sub-dimension, .86 for the "Moral Awareness" sub-dimension, .88 for the "Moral Imagery" sub-dimension, .86 for the "Moral Sensitivity" sub-dimension, .62 for the "Moral Determination" sub-dimension and .94 for the whole scale. On the other hand, to determine which tests to apply to the data set obtained before the statistics were performed, it was examined whether the data showed a normal distribution or not. The normality of the distribution was determined by looking at the skewness and kurtosis values. Since the measurements were normally distributed, parametric tests were used in the study. In the analysis of the data, “Independent Samples T-Test” was used for paired groups, and “One-Way Analysis of Variance (One-Way ANOVA)” was used for variables with more than two groups. To determine between which groups there was a significant difference as a result of the ANOVA test, the Bonferroni test was used when the variances were equal and the sampling was not equal, Tamhane’s T2 test was used when the variances and sampling were not equal. In all tests, the significance value was accepted as 0,05. In line with the data obtained from the research, it was concluded that the moral literacy skills of university students were close to high level. As a result of the study, a significant difference was found in the total scale of the moral literacy levels of university students in terms of gender variable in favor of female students, in terms of grade level variable between 1st year students and 4th year students in favor of 1st year students, in terms of faculty type variable, between the students of the Faculty of Islamic Sciences and the Faculty of Education in favor of the Faculty of Islamic Sciences students, between the students of the Faculty of Education and the Faculty of Sports Sciences in favor of the Faculty of Education students, between the students of the Faculty of Arts and Sciences and the Faculty of Education in favor of the Faculty of Arts and Sciences students, between the students of the Faculty of Islamic Sciences and the Faculty of Sports Sciences in favor of the Faculty of Islamic Sciences students, and between the students of the Faculty of Arts and Sciences and the Faculty of Sports Sciences in favor of the Faculty of Arts and Sciences students. Based on the results of the research, suggestions such as adding an independent course and elective courses to the curriculum to contribute to the acquisition of moral literacy skills by university students, conducting various social activities aimed at providing students with moral literacy skills, etc. have been developed.